(untitled) (De Legibus - Law Journal, 2022)
At one time, this article aims to clarify the concept of personal data, undoing the mistakes inherent in the use of a concept not used in the Law of Protection of Personal Data, such as: metadata. At another time, a brief review is developed, from an evolutionary perspective, on the commonly called “Metadata” Law, seeking to demonstrate that the recent issues of unconstitutionality considered and decided by the Constitutional Court do not appear to be innovative in the legal system. Finally, we will formulate in the summary conclusions, a global appreciation of the theme, leaving some clues to ensure the purpose pursued by the national law with the Constitution of the Portuguese Republic.